Relationship between accounting information systems implementation and corporate governance of rural banks in Indonesia - Rima Rachmawati (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2019)
The purpose of this paper is to examine the relationship between accounting information systems implementation and the governance of rural banks (bank perkreditan rakyat/BPR). Specifically, this study examines the effect of bookkeeping systems, financial reporting, budgeting systems, and IFRS for SMEs implementation on good corporate governance of rural banks. PLS-SEM wasemployed for data analysis to 145 rural banks registered in Regional Owned Bank Association of Central Java Indonesia. The results of data analysis found that bookkeeping systems, financial reporting and budgeting systems implemetation positively affectgood corporate governance of rural banks, while IFRS for SMEs implementation was not significantly affectgood corporate governance of rural banks.